Molecular evidence of Bartonella spp. in wild lowland tapirs (Tapirus terrestris), the largest land mammals in Brazil - Mongruel, Anna Claudia Baumel [UNESP]; Medici, Emília Patrícia; Canena, Ariel da Costa; Dias, Clara Morato [UNESP]; Machado, Rosangela Zacarias [UNESP]; André, Marcos Rogério [UNESP] (Elsevier, 2023)
The genus Bartonella (Hyphomicrobiales: Bartonellaceae) encompasses facultative intracellular α-proteobacteria that parasite erythrocytes and endothelial cells from a wide range of vertebrate hosts and can cause disease in animals and humans. Considering the large diversity of vertebrate species that may act as reservoirs and arthropod species that may be associated with Bartonella transmission, the exposure of animals and humans to these microorganisms is likely underestimated. The present study aimed to investigate the occurrence of Bartonella sp. in wild tapirs (Tapirus terrestris; Perissodactyla: Tapiridae) from two biomes in Brazil: Pantanal and Cerrado. Ninety-nine GPS-monitored wild tapirs were sampled in Pantanal (n = 61/99) and Cerrado (n = 38/99). A qPCR (quantitative real-time polymerase chain reaction) assay targeting the nuoG gene was used for the screening for Bartonella spp. DNA. Positive samples were additionally subjected to conventional PCR assays targeting five molecular markers (ribC, gltA, rpoB, groEL, ITS). Eight (8/99; 08,08%) animals were positive in the qPCR assay for Bartonella spp.: 7 from Cerrado (7/8; 87.5%) and 1 from Pantanal (1/8; 12.5%). The 5 Bartonella ribC sequences obtained from tapirs’ blood samples grouped together with Bartonella henselae obtained from cats, humans, wild felids and Ctenocephalides felis (Siphonaptera: Pulicidae) fleas. To the best of author's knowledge, this is the first report of Bartonella sp. in Tapirus terrestris. This finding contributes to the understanding of the occurrence of B henselae in wild mammals from Brazil as well as expands the knowledge regarding the potential vector-borne pathogens that may affect wild tapis from Cerrado and Pantanal biomes.
Keywords: Bartonellosis; Brazil; Cerrado; Pantanal; Tapir; Wild animals